2018
DOI: 10.3389/fict.2018.00015
|View full text |Cite
|
Sign up to set email alerts
|

Move the Object or Move Myself? Walking vs. Manipulation for the Examination of 3D Scientific Data

Abstract: Physical walking is consistently considered a natural and intuitive way to acquire viewpoints in a virtual environment. However, research findings also show that walking requires cognitive resources. To understand how this tradeoff affects the interaction design for virtual environments; we evaluated the performance of 32 participants, ranging from 18 to 44 years old, in a demanding visual and spatial task. Participants wearing a virtual reality (VR) headset counted features in a complex 3D structure while wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 45 publications
(50 reference statements)
1
14
0
1
Order By: Relevance
“…Participants additionally suggested designing the model so that it was not fixed in one place but could instead be manipulated by the user. This added feature may enhance factual and spatial knowledge retention, as the direct manipulation of virtual 3-D structures has been shown to improve the fidelity of users' internal representation of anatomical structures with regards to shape, location and orientation [15,19]. In addition, participants requested the integration of text into the model itself, such that the user could select an anatomical structure, and a pop-up text block would appear that described the selected portion and outlined its functional role.…”
Section: Discussionmentioning
confidence: 99%
“…Participants additionally suggested designing the model so that it was not fixed in one place but could instead be manipulated by the user. This added feature may enhance factual and spatial knowledge retention, as the direct manipulation of virtual 3-D structures has been shown to improve the fidelity of users' internal representation of anatomical structures with regards to shape, location and orientation [15,19]. In addition, participants requested the integration of text into the model itself, such that the user could select an anatomical structure, and a pop-up text block would appear that described the selected portion and outlined its functional role.…”
Section: Discussionmentioning
confidence: 99%
“…They also found higher embodied locomotion cues for walking rather than sitting. Among other research studies focusing on interaction techniques, locomotion, and embodiment (e.g., Zielasko et al, 2016;Weise et al, 2019;Di Luca et al, 2021), Lages and Bowman (2018) focused on the effect of manipulating objects vs physically walking in the virtual environment on performance in demanding visual tasks. They found that in designing the learning environments, the creator should consider the user controller experience, past gaming experience, and spatial ability of the user.…”
Section: Sense Of Embodimentmentioning
confidence: 99%
“…Epistemic actions are the result of sensorimotor contingencies (Slater, 2009;Slater et al, 2010) supported by a VR system. Even though physically walking is considered to be cognitively demanding, it is considered to be the most natural interaction technique (Lages and Bowman, 2018). Zielasko and Riecke (2021) carry out a survey in which participants rated higher embodied (non-visual) locomotion cues for walking, walking in place, and arm swinging than standing, sitting, or teleportation.…”
Section: Bodily Engagement Through Moving the User In Spacementioning
confidence: 99%
See 1 more Smart Citation
“…Two major points contribute to ecological validity: verisimilitude which describes the similarity between the assessment in the test and a real-life situation; and veridicality which describes precision of what is being assessed compared to daily living (Parsons, 2015). Virtual reality may contribute to increase ecological validity, but also to manipulate and control more effectively spatial navigation variables (Lages & Bowman, 2018).…”
Section: Introductionmentioning
confidence: 99%